Comment about ‘Medical, dental, and nursing students’ attitudes and knowledge towards artificial intelligence: a systematic review and meta-analysis’ - Yoshiyasu Ito; Hironobu Ikehara (BMC Medical Education)
Abstract We read with great interest the recently published article by Amiri et al., titled “Medical, Dental, and Nursing Students’ Attitudes and Knowledge Toward Artificial Intelligence: A Systematic Review and Meta-Analysis.” We would like to offer comments on certain aspects of the findings that we believe warrant further discussion.